High-strength geopolymer based engineered cementitious composites (ECC) for sustainable and resilient construction - Kanagaraj, Balamurali; Anand, N.; Thomas, Mathew; Choo, Chin Siew (Emerald Publishing Limited, 2024)
Purpose – The development of high-strength engineered cementitious composite (ECC) gains a significant leap in structural engineering. Engineers have been looking for new formulations that combine outstanding compressive strength with increased flexural resistance. This research focuses on the main characteristics, techniques and prospective applications of high-strength ECC. The proposed work explores the composition of such concrete, emphasizing the use of novel additives, fiber reinforcements and optimal particle packing to produce excellent mechanical characteristics and demonstrating how high-strength ECC contributes to incorporate sustainability by potentially lowering the need for supplemental reinforcing and resulting in a lower environmental effect. Design/methodology/approach – This research involves on studying the composition of high-strength ECC and geopolymer-based ECC, the use of novel additives, fiber reinforcements and optimal particle packing. It examines the capacity of high-strength ECC to sustain high loads with an allowable deformation without any catastrophic collapse. It discusses the sustainability aspects of high-strength ECC and its potential alternative as geopolymer-based ECC. Findings – High-strength ECC offers an excellent compressive strength while also providing increased flexural capacity. Employment of copper slag (CS) as a filler material for the production of ECC results in 28.92% lower cost, when compared to the mix developed using conventional river sand. Whereas in the case of geopolymer-based ECC, the cost of production was found to be 31.92% lower than that of the conventional. Originality/value – High-strength ECC is developed using conventional river sand and industrial byproduct, CS as a filler material. The combination of achieving higher compressive strength with an increased use of industrial by-products leads to the development of sustainable high strength ECC. The potential use of high-strength ECC reduces the need for supplementary reinforcing and increases the structural lifetime, resulting in a lower environmental impact.